DOES ONLINE MARKETING TRULY REPLACE TRADITIONAL MARKETING? - Gunawan, Emilia Margareth (Universitas Sam Ratulangi, 2013)
ABSTRACT This review explains the way how online marketing has been replacing traditional marketing in terms of marketing mix. This replacement might happen, because online marketing can give advantages, i.e., offering on-time delivery, increasing effectiveness of two way interactions between buyer and seller, and creating online communities (Szmigin, et al, 2005). The transition of atoms to bits format reflects that tangible products in traditional marketing is being digitalized. The marketing strategies also move from multi level product concept to customer customization. In online marketing, buyers can control over prices, hence pricing trend has been moving from fixed price to dynamic price. In terms of promotion, online marketing becomes a complementary of traditional communication tools, where the strategy has a tendency to move from personnel selling to direct marketing. However, there are some debates whether online marketing will replace the position of traditional marketing. This review applies Indonesia as a measurement of this transition. It could be argued that in short run, commonly, the customers in Indonesia still remains in traditional marketing, because it dominates the business systems and cultures. There are some factors impeding the shift, i.e., lack in infrastructure and capital investment. However, in long run, online marketing is supposed to replace traditional marketing but incompletely. Keywords: traditional marketing, online marketing, marketing mix